2006
DOI: 10.1111/j.1540-627x.2006.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Growth: Understanding Venture Size Choices of Women Entrepreneurs

Abstract: In recent years the number of women-owned firms with employees has expanded at three times the rate of all employer firms. Yet women remain underrepresented in their proportion of high-growth firms. A number of plausible explanations exist. To develop richer insights, a two-stage research project was undertaken. A mail survey was sent to a sample of female entrepreneurs to assess motives, obstacles, goals and aspirations, needs, and business identity. Based on the survey results, follow-up, indepth interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
353
6
25

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 466 publications
(411 citation statements)
references
References 25 publications
27
353
6
25
Order By: Relevance
“…With regard to the third hypothesis, women entrepreneurs have attracted increasing attention from authors in terms, for example, of the limitations of female-owned ventures (Menzies et al 2004) or of the quality of family or personal lives (Morris et al 2006). Brush (1992) pointed out that the similarities between the two sexes outweigh the differences, while du Rietz and Henrekson (2000) studied performance differences between ventures started by men versus women in terms of revenue growth.…”
Section: Jel Classifications L25 á L26 á M13 á M16mentioning
confidence: 99%
“…With regard to the third hypothesis, women entrepreneurs have attracted increasing attention from authors in terms, for example, of the limitations of female-owned ventures (Menzies et al 2004) or of the quality of family or personal lives (Morris et al 2006). Brush (1992) pointed out that the similarities between the two sexes outweigh the differences, while du Rietz and Henrekson (2000) studied performance differences between ventures started by men versus women in terms of revenue growth.…”
Section: Jel Classifications L25 á L26 á M13 á M16mentioning
confidence: 99%
“…The other important factor explaining the desire for growth of women entrepreneurs is the presence of equity partners. The presence of other owners may indicate greater financial sophistication and a clear plan for organizational growth (Morris et al, 2006). Davidsson (1989) and Kolvereid (1992) have demonstrated that conditions on the labor market affected growth willingness.…”
Section: Women Entrepreneurs and Growth Orientationmentioning
confidence: 99%
“…Cliff(1998) defined propensity for growth as an entrepreneur's intent to expand the organization, and ability to manage growth as the degree to which he/she can obtain resources and develop the organization. Ylitalo (2010) and Morris (2006) have defined growth orientation as having growth as top priority, and accepting risk to achieve growth.…”
Section: Women Entrepreneurs and Growth Orientationmentioning
confidence: 99%
See 2 more Smart Citations